Gastrointestinal Hemorrhage: Is it a Cause of Malpractice? Decades of Colonoscopy - Hernández, José Luis García; Cortés, Imelda Yasmín Palma; Cabello, José de Jesús Urbina; Barrón, Gema Méndez; Suárez, Ivonne Alondra León; Segura, Carlos Andrés Salas; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2025)
Introduction: Gastrointestinal bleeding is currently a common and underestimated entity, since its diagnostic/therapeutic importance has been left aside and due to erring in its true etiology, it is therefore belligerent. Objective: To describe the experience of the results obtained in the Colon and Rectal Surgery service of the colonoscopies performed in the various hospitals. Method: A study with a multicenter, retrospective, longitudinal, observational and descriptive design was conducted in patients with gastrointestinal bleeding who underwent colonoscopy. Results: A total of 24,185 colonoscopy reports were reviewed, including 3,971 patients who underwent colonoscopy due to the indication of lower gastrointestinal bleeding, of which 1,946 were women (49%) and 2,025 men (51%). The first cause of lower gastrointestinal bleeding was polyposis disease, the second was colon and rectal cancer, and thirdly, diverticular disease. Discussion: The etiology of upper, lower or middle intestinal gastrointestinal bleeding is very varied, so it is very difficult to diagnose, with its symptoms and signs that are usually nonspecific and may resemble those of other diseases, which increases the probability of misdiagnosis. Conclusion: endoscopy plays an indispensable role for the diagnosis, treatment, and follow-up of gastrointestinal bleeding, as well as initial and long-term medical management is decisive in terms of a comprehensive clinical evaluation and an adequate tropicalized response with the resources and supplies that allow the patient to be helped.